Post-Inflammatory Hyperpigmentation in Dark Skin: Molecular Mechanism and Skincare Implications - Markiewicz E; Karaman-Jurukovska N; Mammone T; Idowu OC (Dove Medical Press, 2022)
Ewa Markiewicz,1 Nevena Karaman-Jurukovska,2 Thomas Mammone,2 Olusola C Idowu1 1Hexis Lab, The Catalyst, Newcastle Helix, Newcastle upon Tyne, UK; 2Estee Lauder Research Laboratories, Melville, NY, USACorrespondence: Thomas Mammone, Estee Lauder Research Laboratories, Melville, NY, USA, Tel +1 877 311 3883, Email tmammone@estee.com Olusola C Idowu, HexisLab Limited, The Catalyst, Newcastle Helix, Newcastle upon Tyne, NE4 5TG, UK, Tel +44 1394 825487, Email sola@hexislab.comAbstract: Human skin is characterized by significant diversity in color and tone, which are determined by the quantity and distribution of melanin pigment in the epidermis. Melanin absorbs and reflects ultraviolet radiation (UVR), preventing the damage to genomic DNA in the epidermis and degradation of collagen in the dermis; therefore, darker skin types are thought to be well protected from the photodamage because of the high melanin content. However, increased content of melanin in combination with the extrinsic stress factors causing inflammation such as excess UVR, allergic reactions, or injury can also frequently lead to cosmetic problems resulting in discoloration and scarring. This review summarizes current knowledge on histopathology and likely molecular signatures of one of the most common problems, post-inflammatory hyperpigmentation (PIH). The mechanisms proposed so far are subsequently discussed in the context of other factors characterizing darker skin types. This includes the common cellular features, organization of upper skin layers, and major biomarkers, with particular emphasis on increased propensities to systemic and localized inflammation. Enhanced or prolonged inflammatory responses can not only affect the process of melanogenesis but also have been implicated in injury-related skin pathologies and aging. Finally, we summarize the major cosmetic treatments for PIH and their known anti-inflammatory targets, which can be beneficial for darker skin tones and combined with broad-spectrum filters against UVR.Keywords: post-inflammatory hyperpigmentation, skin ethnicity, inflammation, extrinsic aging